Community characteristics and the risk of non-communicable diseases in Ghana. - Winfred A Avogo (Public Library of Science (PLoS), 2023)
Non-communicable Diseases (NCDs) are rising quickly in low- and middle- income countries. In Ghana, chronic diseases are major causes of morbidity and mortality, yet data and the evidence- base for awareness, detection, and management of NCDs are lacking. Using data from the 2014 Ghana Demographic and Health Survey (GDHS), the first national study with information on hypertension and other risk factors, we examine the correlates and community characteristics associated with the risk of hypertension, obesity, and anemia among women. We find that hypertension prevalence in Ghana was 16 percent and 17 percent were overweight/obese, while 41 percent had anemia of any form. On community characteristics, the level of poverty in a community was significantly associated with lower risks of all three NCDs, while the aggregate level of employment had higher risks. On individual characteristics, the wealth of a household, women's educational level and urban residence were significant predictors of NCDs. We interpret the findings within the literature on neighborhood characteristics, the social gradient of health and in the context of speeding up the attainment of the Sustainable Development Goals (SGDS) to reduce premature deaths by one-third by 2030.